BIOMETRICAL INDICES VARIATION FOR SCOTS PINE NEEDLES IN ANNOSUM ROOT ROT FOCI - Mihaylichenko, А. A. (Forestry and Forest Melioration, 2018)
Introduction In stands created on old arable lands, an investigation of the influence of pine affection by annosum root rot on trees assimilation apparatus has a scientific significance in terms of studying trees condition differentiation under the influence of the disease. The investigation is also destined to solve the practical tasks of early diagnosis of root rot. As a result of root affection caused by root rot, some changes occur in water and minerals supply to the trees. This, in turn, negatively affects the assimilation apparatus growth and biomass accumulation. Shortened needles and needle color variation for pine trees in the disease foci may serve as a diagnostic sign of root rot affection. For early diagnosis of trees affected by the pathogen, it is important to examine changes in assimilation apparatus at different stages of the disease. The aim of the research was to determine the effect of pine stands affection by root rot on developing of assimilation apparatus depending on the age of the stands. Materials and methods The study was conducted in ІІІ–ІХ age classes pine stands affected by annosum root rot in State Enterprise "Vovchanske Forest Economy" of Kharkiv Regional Administration of Forest and Hunting Management. In stands of each age class, five sample trees were selected by average inventory indices for each variation in die-back foci directly as well as in inter-focal spaces, using the averaged data of sample plots. 100 pairs for each of 1, 2 and 3-year needles were selected from these trees. Needles were taken from the central shoot. The data were treated statistically by means of MS Excel computer programs. Results The analysis showed that, regardless of the age and growth power of trees located directly in die-back foci, 1-, 2- and 3-years needles were less in length by 6.4 %, 7.1 % and 5.8 %, respectively, as compared to the needles of relatively healthy trees in inter-focal space. In view of age classes, the largest difference in the needles average length for trees in die-back foci directly and for trees in inter-focal space was accounted for the age class VII (20.3 %). Not so much difference was marked for stands of the following age classes: III (3.9 %), V (8.5 %), VIII (6.5 %) and IX (5.6 %); the lowest one was indicated for stands of IV and VI age classes (1.3 %). The comparison of mass accumulation for fresh and air-dry pine needles of pine cultures created on old arable lands shows that needles’ mass for trees located in inter-focal space was greater on average by 13.1 % for fresh weight and by 12.7% for air-dry weight as compared to trees located in die-back focus. The comparison of averaged data for a total mass of needles for trees located in die-back foci and in inter-focal space showed that the biggest difference is accounted for the age class VII; it is 39.3 % for fresh pine needles and 35.7 % for air-dry ones. Somewhat smaller differences were registered in stands of age class V (15.7 % for fresh weight and 14.9 % for air-dry weight), age class VI (15.4 % for fresh weight and 16.4 % for air-dry weight) and of age class VIII (18.1 % for fresh weight and 14.3 % for air-dry weight). Conclusions The results of the analysis suggest the conclusion that the length and mass of fresh and air-dry needles of trees in an inter-focal space exceed the similar indicators of trees in die-back foci. Needles’ weight and length in die-back foci strongly correlate with such indicators in inter-focal space (correlation coefficient of 0.91 and 0.81, respectively). Correlation between weight and length of air-dry pine needles in die-back foci and in inter-focal space is slightly less and amounts to 0.86 and 0.69, respectively. The solids content in the needles of the trees in inter-focal space is smaller than that of trees in die-back foci, indicating the imbalance of compounds synthesis under the influence of disease. Changes of biometric indicators for needles of infected stands correspond the stages of the disease (the appearance of foci, their development and attenuation). The most significant negative impact of the disease on the trees metabolism is observed in VII age class stands.